Model-Based Control with Active Disturbance Rejection Algorithm for a Diesel Engine - Shun-Liang Ding; Shuai-Feng He; Bi-Qing Tu; Jin-Jin Liu; Yu-Yuan Wang; En-Zhe Song (Complexity)
To improve the speed control performance of a diesel engine, the active disturbance rejection controller (ADRC) is designed by adding an arranging transition process to the traditional PID controller, extracting differential signals reasonably, and adopting nonlinear combination process to error signals. The ADRC is composed of a tracking differentiator (TD), an extended state observer (ESO), and a nonlinear state error feedback (NLSEF). Such constructed ADRC can adapt to the strong nonlinear and complicate working conditions of diesel engine for power generation. A simulation model of the diesel engine is built to verify the proposed ADRC, and simulation results are in good accordance with the experimental results. To further validate the advantages of the designed ADRC, the traditional PID is improved by TD. Meanwhile, performance comparisons are carried out between traditional PID controller, improved PID controller, and ADRC. Results present that the improved PID controller can achieve a better control performance than that of the traditional PID controller both in steady state and transient state. However, the ADRC can further improve the speed control performance evidently on the basis of the improved PID controller.